Projected Climate Changes of CMIP5 models in La Cruz, Guanacaste, Costa Rica - Hidalgo, Hugo-G.; Alfaro, Eric-J.; Pérez-Briceño, Paula-M. (Revista de Biología Tropical, 2021)
Introduction: La Cruz is located in northwestern Costa Rica, and it is characterized by a dry tropical climate with a well-defined dry season. This municipality has reported many impacts of hydrometeorological events during the last 45 years, mostly associated with wet events such as floods that affected roads, housing, and crops; as well as some droughts that have impacted the population and their livelihoods. Objective: The objective of this article is to provide information regarding possible future climate changes during the 21st century associated with a pessimistic emission scenario in the municipality of La Cruz in Guanacaste, Costa Rica. Methods: We used DesInventar database to identify the hydrometeorological impacts in La Cruz and classified them by month. Downscaled simulations from the Climate Model Intercomparison Project 5 (CMIP5) were used to simulate past and future changes (1979-2099) in temperature and precipitation. In addition, a hydrological model was used to calculate runoff projections from meteorological data. Results: Floods, and housing, roads and agricultural damages are the most recurrent impacts. In addition, some human deaths are reported during this time. Results show that a drier and warmer future will be characteristic of the climate in La Cruz in the 21st century, especially after 2040. Runoff is also expected to be reduced significantly following the meteorological trends. Conclusions: It is expected that higher aridity will be present in the future, affecting human and environmental systems.